Effects of N fertilizer on root growth in Zea mays L. seedlings - Wang, Z.R.=700 1 Rui, Y.K.; Shen, J.B.; Zhang, F.S.
(En, Es)
Ilus., 18 ref.
Keywords: ZEA MAYS; ABONOS NITROGENADOS; CRECIMIENTO; RAICES; INHIBIDORES DEL CRECIMIENTO; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH